An information diffusion model in social networks with carrier compartment and delay - Du, Bo; Wang, Haiyan; Liu, Maoxing (Nonlinear Analysis: Modelling and Control, 2018)
With the wide applications of the communication networks, the topic of information networks security is getting more and more attention from governments and individuals. This paper is devoted to investigating a malware propagation model with carrier compartment and delay to describe the process of malware propagation in mobile wireless sensor networks. Based on matrix theory for characteristic values, the local stability criterion of equilibrium points is established. Applying the linear approximation method of nonlinear systems, we study the existence of Hopf bifurcation at the equilibrium points. At the same time, we identify some sensitive parameters in the process of malware propagation. Finally, numerical simulations are performed to illustrate the theoretical results.
Keywords: social networks; malware propagation; Hopf bifurcation; local stability